Вот как это было: [повесть] / Юрий Герман ; художник Ольга Фадеева - Герман Юрий Павлович (Вот как это было, 2015)
Экземпляры: СФ-3 (20151019) / Инвентарный номер: 42688z3 / Цена: 270.00 / Сис.шифр: 84(2) / Авт.знак: Г 38 / ББК: 84(2=Рус)